PEDAGOGIES OF CARE IN THE ECOLOGY OF KNOWLEDGES: HEALTH EDUCATION FOR LIVING WITH THE SEMI-ARID REGION (REMUNOM, 2026)
The debate on health education in semi-arid territories has historically been dominated by the biomedical paradigm, often detached from traditional knowledge and local socio-ecological dynamics. The central problem of this study was to analyze how pedagogies of care grounded in the ecology of knowledges configure health education strategies for living with the Semi-Arid region and what evidence exists regarding their effectiveness in promoting autonomy and resilience among traditional populations. The objective was to critically synthesize recent scientific production on this topic. Methodologically, an integrative literature review was conducted between November 2025 and January 2026 in SciELO, Scopus, Web of Science, and PubMed databases, structured according to the PCC model. A total of 225 records were initially identified, and 24 studies composed the final corpus. The results showed that territorialized social technologies, such as medicinal plant workshops, agroecological home gardens, and community water management, strengthen therapeutic autonomy, food security, and climate resilience. It is concluded that pedagogies of care operate as political-educational strategies capable of articulating cognitive justice, community participation, and socio-environmental sustainability, although their consolidation depends on sustained institutional support.